The German-American physician and philologist Achilles Rose (1839-1916), the grand Philhellene - Tsoucalas, Gregory; Vladimiros, Lazaros (DELTOS, 2024)
Achilles Rose, a German-American physician of the late 19th century, became famous for his persistent global struggle to promote the Hellenic language as the official language in medicine and science in general. Having studied in Zurich, Jena, and New York, he became a general practice physician. His most well-known medical treatise was “The Carbonic Acid in Medicine”, and he was the author of various works celebrating the Greeks and their vivid language. The Medical Society of Athens elected him as a member of a committee for such a purpose. Although Latin appeared to have won this linguistic battle, Hellenic terms eventually conquered international nomenclature. Greece must not forget this valiant Philhellene.